(untitled) (Conferencea, 2021)
In the content of the article, the pedagogical conditions of attracting students to physical education and sports, absorbing and developing the concepts of the culture of healthy life, the possibilities and effectiveness of physical education and sports have been studied, the technological conditions of the organization of the targeted pedagogical process have been referred to